Records of alien marine species of Indo-Pacific origin at Sigri Bay (Lesvos Island, north-eastern Aegean Sea). (17th March 2015) - Evagelopoulos, A.; Poursanidis, D.; Papazisi, E.; Gerovasileiou, V.; Katsiaras, N.; Koutsoubas, D.
Abstract : Ten alien species were recorded in a first-time survey of the benthic biodiversity of the upper sublittoral at Sigri Bay (Lesvos Island, north-eastern Aegean Sea). The record of the mollusc Syrnola fasciata is the first in Hellenic territorial waters. The records of the brown alga Stypopodium schimperi, the bivalve Septifer cumingii, the gastropods Syrnola fasciata and Smaragdia souverbiana and the bony fish Siganus luridus constitute evidence for a further northwards extension of their geographic ranges in the Aegean Sea. The record of Cerithium scabridum is the first in Lesvos Island and partially fills the gap in the distribution of the species in the eastern Aegean Sea. We also recorded the green alga Caulerpa cylindracea, the angiosperm Halophila stipulacea and the bivalve Pinctada imbricata radiata, which are widely distributed in the eastern Mediterranean. The polychaete Marphysa adenensis, which was also found at Sigri Bay, has recently been reported for the first time from the Mediterranean as a cryptogenic species.